Verifying switched-mode computer controlled systems - Kapinski, J.; Krogh, B.H. (2002 IEEE International Symposium on Computer Aided Control System Design, 2002)
This paper presents a new approach to verifying properties of computer control systems with periodic sampling when the control programs include both continuous-variable computations and discrete-state transitions (mode switching). We focus on the novel aspects of the approach, which are (1) a formal model for hybrid systems with continuous-time and discrete-time behavior and (2) a method for computing conservative approximations to the sets of reachable states. The formal model and computational routines are incorporated into CheckMate, a MATLAB-based tool for verification of properties of hybrid dynamic systems. This tool is being applied to the verification of embedded controllers in automotive engines.